2019
DOI: 10.35940/ijrte.b3495.078219
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of StormPav Green Pavement System Using Storm Water Management Model and SolidWorks Flow Simulation

Abstract: Storm Water Management Model (SWMM) and SolidWorks Flow Simulation (SW-FS) models to represent StormPav Green Pavement System are tested through a case study of commercial premises. Modelling effort of simplifying the complex StormPav system to take in only the effective storage volume is attempted using the 1D SWMM. A 3D modelling of capturing the multi-compartmental and multi-unit StormPav system is attempted using SW-FS. The modelling outputs in terms of velocity distribution within the StormPav system of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These past studies [7][8][9][10][11] have been verified numerically based on water balance; however, these studies have not been validated due to the absent of a StormPav system in the field. As such, the R&D team has set up an actual-scaled StormPav system in a residential setting in Figure 3.…”
Section: Field Testmentioning
confidence: 99%
See 1 more Smart Citation
“…These past studies [7][8][9][10][11] have been verified numerically based on water balance; however, these studies have not been validated due to the absent of a StormPav system in the field. As such, the R&D team has set up an actual-scaled StormPav system in a residential setting in Figure 3.…”
Section: Field Testmentioning
confidence: 99%
“…There are also other studies [9][10][11] that represent StormPav system using the "conduit" in SWMM5. Authors reported that StormPav could convey water via its middle layer and a closed rectangular "conduit" is best to represent the system.…”
Section: Introductionmentioning
confidence: 99%
“…Among the potential options, in addition to the conventional stormwater management systems, there are systems that have positive impacts on the surrounding environment, including facilities designed for periodic retention [15,16], infiltration of stormwater into the soil [17,18], and for harvesting rainwater [19,20]. The use of facilities classified as green infrastructure is particularly recommended.…”
Section: Introductionmentioning
confidence: 99%